Medical Student Identification of Knee Effusion by Ultrasound. (30th March 2011) - Hoppmann, Richard; Hunt, Patrick; Louis, Hunter; Keisler, Brian; Richeson, Nancy; Rao, Victor; Stacy, Jason; Howe, Duncan
Abstract : Twenty-one fourth-year medical students were given a brief lecture on ultrasound of the knee and fifteen minutes of supervised ultrasound scanning of three cadavers which had been injected with saline to give varying degrees of knee effusions. Each student was then individually observed and required to scan both knees of a cadaver different from the practice cadavers and identify the patella, the femur, the quadriceps tendon and if a suprapatellar effusion was present, and which knee had the larger effusion. All twenty-one students correctly identified all anatomical structures, suprapatellar effusions, and which knee had the larger effusion. Identifying a knee effusion can be an important clinical finding in diagnosing and managing a patient with knee complaints. Fourth-year medical students can learn to identify knee effusions with ultrasound following a brief introductory lecture and hands-on scanning practice session.